PowerBuilder 9 : advanced client/server development - Armstrong, Bruce, 1959 February 20- (Sams, 2004)
Over a decade ago PowerBuilder introduced the idea of rapid Client/Server application development and, for much of that time, was the leader in both technology and sales in the enterprise development market. Although PowerBuilder has lost significant market share to Visual Basic and Delphi, it still enjoys an intensely loyal developer community of close to 300,000. Version 9 of PowerBuilder continues the tradition of introducing leading-edge technology to these developers. PowerBuilder 9 Client/Server Development zeroes in on the most important aspects of building client/server applications in PowerBuilder, including PBNI (native interface), PFC (foundation classes), and database connectivity.